Parenting Dalam Mengajari Anak Untuk Menghadapi Rintangan Dan Bangkit Dari Kegagalan Di LKSA At-Thahir Jombang - Mustofa, Ali; Indana, Nurul; Zahiq, Moh; Nurul Qomaria, Elysa; Wijono, Hani Adi (An Naf'ah: Jurnal Pengabdian Masyarakat, 2025)
This article aims to determine the effectiveness of parenting study activities in increasing parents' awareness of early childhood care. A resilient child is a child who can adjust, face challenges, and bounce back after experiencing a difficulty or problem. the implementation of this community service uses a community service method using a PAR approach with stages: Stage to Know, Stage to Understand, Stage to Plan, Stage to Act, Stage to Change. The results state that children's resilience does not appear suddenly, but needs to be trained from an early age by parents. A resilient child does not mean never failing, never being sad, or never being disappointed, a resilient child is a child who can get up, after feeling failure, sadness, and disappointment. Teaching children to face obstacles and rise from failure can be done by several things: being an example for children, building a mutually supportive relationship between parents and children, giving children the opportunity to develop a sense of responsibility, helping children control emotions, and giving children the opportunity to face challenges